1996
DOI: 10.1016/0196-9781(96)00141-6
|View full text |Cite
|
Sign up to set email alerts
|

Truncation studies of α-melanotropin peptides identify tripeptide analogues exhibiting prolonged agonist bioactivity

Abstract: Truncation studies of alpha-melanotropin peptides identify tripeptide analogues exhibiting prolonged agonist bioactivity: PEPTIDES 17(6) 995-1002, 1996.-Systematic analysis of fragment derivatives of the superpotent alpha-MSH analogue. Ac-Ser.Tyr-Ser-Nle4-Glu- His-DPhe7-Arg-Trp-Gly-Lys-Pro-Val-NH2(NDP-MSH), led to the discovery of tripeptide agonists possessing prolonged bioactivity in the frog skin assay. Of particular significance to this discovery was Ac-DPhe-Arg-DTrp-NH2, which was the most potent tripepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 31 publications
3
60
0
Order By: Relevance
“…49 In the native loop sequence of AGRP, an Arg-Phe-Phe tripeptide is postulated to be the active pharmacophore. It was hypothesized that insertion of the DPhe-Arg-Trp tripeptide into the DPro-Pro cyclized loop mimetics of AGRP may result in increased potency and/or selectivity in the resulting chimeric peptides, since this agonist sequence is the same length as the postulated antagonist active sequence and would not alter peptide length and may result in less disruption of the loop structure.…”
Section: Resultsmentioning
confidence: 99%
“…49 In the native loop sequence of AGRP, an Arg-Phe-Phe tripeptide is postulated to be the active pharmacophore. It was hypothesized that insertion of the DPhe-Arg-Trp tripeptide into the DPro-Pro cyclized loop mimetics of AGRP may result in increased potency and/or selectivity in the resulting chimeric peptides, since this agonist sequence is the same length as the postulated antagonist active sequence and would not alter peptide length and may result in less disruption of the loop structure.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of the two modifications resulted in the NDP-MSH ligand, a sub-nanomolar, nonselective melanocortin receptor agonist. Truncation studies of NDP-MSH indicated an Ac-DPhe-Arg-Trp-NH 2 tripeptide sequence to be the minimally active fragment in both the frog skin bioassay and at the cloned MCRs [46, 114]. An alanine-positional scan of NDP-MSH reported decreased potencies when either the DPhe 7 or Trp 9 positions were substituted, indicating the importance of these two aromatic residues for the high potency of NDP-MSH [47].…”
Section: Classic Peptide Melanocortin Ligandsmentioning
confidence: 99%
“…Similar 5- and 4-fold decreases at the mMC3R and mMC4R were observed when Glu 5 was replaced with Ala. Truncation of the first five positions from NDP-MSH has been reported to decrease potency at the mMC1R (16-fold) and the mMC3R (68-fold) relative to NDP-MSH. 28 This same truncation did not alter potency in the frog skin bioassay relative to NDP-MSH, 59 implying these residues may play a small, but not critical role, in ligand potency. The [Ala 5 ]NDP-MSH peptide has previously been assayed at the hMC4R and possessed 4-fold decreased agonist potency relative to NDP-MSH, in agreement with the results observed herein.…”
Section: Resultsmentioning
confidence: 92%
“…Truncation of these NDP-MSH residues have been reported to affect the mMC5R (6-fold potency loss compared to NDP-MSH) 28 and resulted in a 13-fold potency loss in the frog skin bioassay, 59 suggesting these residues are not critical for agonist potency.…”
Section: Resultsmentioning
confidence: 99%